Normal Hematopoetic Stem and Progenitor Cells Can Exhibit Metabolic Flexibility Similar to Cancer Cells - Vlaski-Lafarge, Marija; Labat, Veronique; Brandy, Alexandra; Refeyton, Alice; Duchez, Pascale; Rodriguez, Laura; Gibson, Nyere; Brunet de la Grange, Philippe; Ivanovic, Zoran (Frontiers in Oncology, 2020)
It is known that cancer stem cells (CSCs) with the largest proliferative capacity survive the anoxic and/or ischemic conditions present inside tumorous tissue. In this study we test whether normal stem cells can survive under the same conditions due to cancer cell-like metabolic adaptations. We cultivated a CD34+ population with a majority of hematopoietic progenitors, and a CD34+CD38lowCD133+CD90+CD45RA- population, highly enriched in hematopoietic stem cells (HSCs), under anoxic, anoxic/aglycemic (“ischemia-like”) or physiological conditions (3% O2). Results showed, despite a reduction in total cell fold expansion proportionate to the decrease in O2 concentration; CD34+ cells, aldehyde dehydrogenase-expressing primitive cells, and committed progenitors expanded, even in anoxia. Interestingly, under ischemia-like conditions, stem and CD34+ cell populations are maintained at day-0 level. Cell-cycle analysis further revealed an accumulation of cells in the G0/G1 phase in anoxia or anoxia/aglycemia, with a fraction of cells (~40%) actively cycling (SG2M phases). Also stem cell analysis showed that in these conditions a long-term Scid Repopulating activity was equal to that found with 3% O2. In addition stem cells with the highest proliferative capacity were maintained in anoxia/aglycemia and in anoxia. The estimated ATP profile, active mitochondrial content and succinate accumulation are indicative of anaerobic mitochondrial respiration in both HSCs and CD34+ progenitors under ischemia-like conditions. We demonstrate here that primitive hematopoietic cells show similar metabolic flexibility to CSCs, allowing them to survive a lack of O2 and O2/glucose. Our study reveals that this feature is not the consequence of malignant transformation, but an attribute of stemness.